PENGEMBANGAN MEDIA PEMBELAJARAN KARTU EDUKATIF BERBANTUAN APLIKASI QUIZLET PADA MATERI MENGAPA KITA PERLU MAKAN DAN MINUM - Nursyifa Damayanti; Irvan Permana; Nur Hikmah (STKIP Subang, 2026)
This study aims to produce an innovation of Educational Card Learning Media Assisted by the Quizlet Application on the material why we need to eat and drink for grade V. The study was conducted at SDN Cibatok 02 with a total of 35 people in the 2024-2025 academic year. This study is a Research and Development (RnD) study, with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Educational Card Learning Media assisted by the Quizlet application is a digital learning media for students that can make it easier for students to carry out learning activities in electronic form that can be accessed on computers, laptops, smartphones, or cellphones. This study began by analyzing the needs of learning media for participants and student curriculum, after which the researcher created a product design that would be used to develop the product. Before being developed for students, the product was validated by experts in the field and then tested in a limited trial with respondents. The results of the validation trial stated that the product was very feasible with an average value of 96%. The results of the limited trial stated that the Educational Card learning media assisted by the Quizlet application was in the very feasible category with an average value of 88%. Based on the results of the pretest and posttest recapitulation with an average N-Gain value of 0.76, which means it is included in the high or effective criteria. Based on the results of the study, it can be concluded that the Educational Card learning media assisted by the Quizlet application is very feasible and effective for use in the learning process.